Implementation Of Augmented Reality Procedures For Prayer Using Marker-Based Tracking Method - Adi Darmanto; Faisal Reza Pradhana; Dihin Muriyatmoko; Oddy Virgantara Putra; Lukman Effendi (Universitas Muhammadiyah Sidoarjo, 2021)
Prayer learning activities at PAS Baitul Qur'an Ponorogo Kindergarten have so far been carried out with face-to-face practice between teachers and students. However, the teachers teach the proper way of praying during the pandemic. This study aims to introduce Augmented Reality (AR) technology to teachers and children as a medium for learning to pray. From this research resulted in the application